Size of the semicircular canals measured by multidetector computed tomography in different age groups - Daocai, Wang; Qing, Wang; Ximing, Wang; Jingzhen, He; Cheng, Liu; Xiangxing, Ma (Journal of computer assisted tomography, 2014)
The purpose of the study was to obtain reference values for the sizes of the semicircular canals (SCCs) on multidetector computed tomographic (CT) images in different age groups. Computed tomographic images of the temporal bone of 210 patients, a total of 420 ears without inner ear pathology, have been evaluated. These patients were divided into 4 groups by age: young children (<7 years), older children and adolescents (8-17 years), adults (18-59 years), and the elderly patients (>60 years). The inner diameter, maximum height, and width of the SCCs were measured. There was no significant difference in the size of SCC among the 4 age groups. The inner diameter measurements of the anterior SCC, lateral SCC, and posterior SCC were 0.101 ± 0.016, 0.135 ± 0.033, and 0.124 ± 0.021 cm, respectively. The height measurements of the anterior SCC, lateral SCC, and posterior SCC were 0.535 ± 0.086, 0.349 ± 0.090, and 0.490 ± 0.109 cm, respectively. The width measurements of the anterior SCC, lateral SCC, and posterior SCC were 0.567 ± 0.080, 0.302 ± 0.082, and 0.472 ± 0.099 cm, respectively. The size of SCCs remains constant from children to the elderly people, unlike the other human organs. The reference values provided by multidetector CT can serve as an aid for the interpretation of CT images.